Analisis Pengelolaan Modal Usaha Dalam Rangka Meningkatkan Taraf Kehidupan Ekonomi Petani Bawang Merah Dengan Menggunakan Media Tanam Sawah Tadah Hujan - Kamaludin Kamaludin; Sri Wahyuningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aims to know the condition of venture capital as well as to know the management of business capital and the profit generated by shallot farmers who use rain-ed rice fields. This research uses qualitative research methods with the focus of research describing business capital conditions, business capital management, and the profits generated by shallot farmers who use rainwater fields in Bulakamba District of Brebes Regency. The data collection techniques used in this study are observation techniques, interview techniques, and documentation techniques. The results of this study are in the form of the concept of business capital governance for shallot farmers who use the rain fields in the form of concept 4 S (Set Up, Save, Synergy, and Submission), through this concept shallot farmers are expected to manage the business capital to the maximum through commitment and self-discipline and this concept as a foundation of self-competence development for shallot farmers to increase the economic value of shallots to achieve an increase in the level of economic life for shallot farmers by using the media to plant rain-ed rice fields. Keywords: Business Capital Management, Economic Living Standards, Shallot Farmers, Rainy Rice Fields